School Practices In The Colégio Americano: an Approach to Material Culture - Aragão de Sousa, Marlucy do Socorro; Guimaraes, Jacqueline Tatiane da Silva; Castro, César Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article addresses school practices and material culture in school in Belém Do Pará at the end of the nineteenth century. The objective is to analyze how material culture and school practices were articulated at the Colégio Americano, conceived by José Veríssimo between 1884 and 1890. The work Noticia Geral sobre o Collegio Americano is used as a source of information. The methodology used comprises a hermeneutic-historical approach. When analyzing the material culture of the school, the outlook includes a perception of its links with the historical, cultural and social context where a new model of education highlighting civility, nation and moral was created. Consequently, such devices were not just simple objects, but they revealed the conflictual or peaceful relations of this context, and even the school practices in the institution. It is observed that, for its creator, the use and the description of the objects placed in the Colégio Americano structure were intended to establish and maintain standards that should form disciplined men. They should be directly linked up with the purpose of physical, moral and civic education of students.